PEMANFAATAN POHON AREN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI DUSUN PAKKOLOMPO DESA BORISALLO KECAMATAN PARANGLOE KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This type of research is qualitative research with the approach used in this study is a sociological approach. Sources of data in this study are the village head and four brown sugar makers in Pakkolompo Hamlet, Borisallo Village, Parangloe District, Gowa Regency. Furthermore, the data collection methods used in this study were observation, interviews, and documentation. Then in this study using processing techniques and data analysis carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that efforts to use aren trees in increasing community income in Pakkolompo Hamlet, Borisallo Village, Parangloe District, Gowa Regency are: cleaning the aren trees, the process of hitting and swinging male flower bunches, the method of male flower bunches, the sap flavoring process, and the process. manufacture of male sugar, the process of flavoring the sap, and the process of making male sugar, the process of flavoring the sap, and the process of making male brown sugar. Community obstacles in utilizing palm trees in Pakkolompo Hamlet, Borisallo Village, Parangloe District, Gowa Regency are problems in preserving sap, availability of palm trees, low education levels, and marketing difficulties.